Technical report: PID design of second‐order non‐linear uncertain systems with fractional order operations. Issue 4 (2nd August 2021) - Chen, Song; Chen, Tehuan; Xu, Chao; Chu, Jian
Abstract: This study considers a control problem related to the regulation of fractional‐order systems controlled by fractional order proportional‐integral‐derivative controllers ( PI λ D μ ). The stability result of PI λ D μ ‐based control systems is provided, such that the closed‐loop systems can accomplish global stabilisation under some suitable conditions related to the system uncertainties. Finally, a simulation is demonstrated to verify the results.